Mycosporine-Like Amino Acids (MAAs): Biology, Chemistry and Identification Features - Vanessa Geraldes; Ernani Pinto (MDPI AG, 2021)
Mycosporines and mycosporine-like amino acids are ultra-violet-absorbing compounds produced by several organisms such as lichens, fungi, algae and cyanobacteria, especially upon exposure to solar ultraviolet radiation. These compounds have photoprotective and antioxidant functions. Mycosporine-like amino acids have been used as a natural bioactive ingredient in cosmetic products. Several reviews have already been developed on these photoprotective compounds, but they focus on specific features. Herein, an extremely complete database on mycosporines and mycosporine-like amino acids, covering the whole class of these natural sunscreen compounds known to date, is presented. Currently, this database has 74 compounds and provides information about the chemistry, absorption maxima, protonated mass, fragments and molecular structure of these UV-absorbing compounds as well as their presence in organisms. This platform completes the previous reviews and is available online for free and in the public domain. This database is a useful tool for natural product data mining, dereplication studies, research working in the field of UV-absorbing compounds mycosporines and being integrated in mass spectrometry library software.